The Keynesian revolution - Klein, Lawrence R. (London : Macmillan, 1968)
The book covers the following topics: Keynes as a Classical Economist; The Birth of the General Theory; The New and the Old; A Polemical Digression; Anticipations of the General Theory; Depression Economics?; Keynes and Social Reforms; The Keynesian Revolution Revisited and The Econometrics of the General Theory.
Based on the author's thesis (doctoral--M.I.T., 1944).
Includes bibliographical references and index.
rpm 03/11/2017
Loans
Keywords: Keynesian economics; Economic theory